Biomimetic Synthesis of Zinc Oxide 3D Architectures with Gelatin as Matrix - Yong Gan (Journal of Nanomaterials, 2010)
Peanut-like and flower-like zinc oxide 3D architectures were synthesized via a facile biomimetic process using gelatin as matrix. Techniques of XRD, SEM, HRTEM, FT-IR, and UV-vis absorption spectra were used to characterize the structure and property of the zinc oxide architectures. The experimental results show that the peanut-like ZnO and flower-like ZnO architectures can be obtained through changing the Zn2+ concentration or the aging time. FT-IR spectra indicate that the Zn2+ is coupled with the C=O bond of the gelatin molecules through the electrostatic interaction. Based on the experimental process, the possible growth mechanism of the ZnO 3D architectures is proposed. UV-vis absorption spectrum of the peanut-like ZnO has a broad absorption band in the UV region, and the blue-shifting of the band is observed.